Development and Validation of Reverse-phase High-performance Liquid Chromatography Method for Simultaneous Estimation of Riluzole and Levodopa in Tablet Dosage Form (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: The objective of this study was to develop a new and simple reverse-phase high-performance liquidchromatography (RP-HPLC) method for the simultaneous estimation of riluzole (RZ) and levodopa (LD) in themarketed tablet dosage form. Materials and Methods: The chromatographic separation was achieved on a RPhypercil C18 column (250 Ã— 4.6 mm i.d., 5 Î¼m) using a mobile phase consisting of methanol and water (75:25v/v) at a flow rate of 1.0 ml/min with the ultraviolet detection wavelength of 273 nm at ambient temperature.The developed method was validated as per the International Council on Harmonization guideline for linearity,accuracy, precision, robustness, ruggedness, limit of detection (LOD), limit of quantitation (LOQ), and specificity.Results: Results of validation studies were found satisfactory with % relative standard deviation values of